Evaluasi Usability Pada Aplikasi Uber Menggunakan Pengujian Usability - Muhammad Yosa Alfiqie; Ismiarta Aknuranda; Niken Hendrakusma Wardani (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
UBER is one of the apps that provides online transportation based in Indonesia. UBER user are getting bigger these day, with total download reaching 100 million times. But there are still some users who have a complain regarding the app, they stated that the GPS is not showing the user's location, then some of them confused how to choose the payment method, and there are even some of them who already paid but not written in the application. From this feedback, it is necessary to identify further what are the problems exist in UBER application, and using usability level measurement to find out the extent of ease, rate of speed, error rate, and level of satisfaction. In this study provides evaluation results to determine the usability problems and levels by using the usability testing method. The result that we get after the evaluation shows the usability problems that exist in UBER application, such as the maps in the application is less accurate, users are confused with the start screen because its lead straight to the maps, users are confused which one is their driver, and there are confusions because the application are using English. The usability level results that consists of the level of ease of the users in completing the task given is 100%, the level of time needed by users when finding the necessary information is 0.0116 goals/sec, the user's error rate is 0,13, and the level of the user satisfaction is between 40%-50%.